Effect of Internal Audit Excellence Capability on Firm Goal Achievement of Hotel Businesses in Thailand - Khammongkol, Wanvipa; Ussahawanitchakit, Phaprukbaramee; Janjarasjit, Suparak (วารสารการบัญชีและการจัดการ, 2018)
This research aims to explore the effects of internal audit excellence capability on firm goal achievement. The model was empirically tested by using the collected data of mail surveys from hotel businesses in Thailand. Internal auditors or the chief directors of the internal audit managers are the key informants. There were 290 returned questionnaires that were used in this analysis. The Ordinary Least Squares (OLS) regression was the method used for testing the hypotheses. The results revealed that each dimension of internal audit excellence capability has positively influenced its consequences which are business value, stakeholder reliability and firm goal achievement. Finally, contributions and suggestions are also provided for further research.